Determinants of Taxpayers Paying Land and Building Taxes - Welly Surjono; Cucu , Cucu; Putri, Wenti Frisca Septiani (Adpebi International Journal of Multidisciplinary Sciences, 2024)
Purpose – This study aim to analyze the understanding, level of awareness of the compliance of individual taxpayers in paying land and building tax, both partially and simultaneously. Methodology/approach – The population in this study were individual taxpayers in 11 hamlets of Pangeureunan Village, Garut Regency, totaling 6,195 taxpayers. Based on the slovin sampling technique, a sample of 98 individual taxpayers was obtained. This type of research is quantitative research with primary data. The research method uses descriptive and verification methods. The data analysis technique used is multiple linear regression analysis with several tests. Findings – From the results of the study it can be concluded that partially the understanding of taxpayers affects taxpayer compliance. Taxpayer awareness affects taxpayer compliance. While simultaneously, taxpayer understanding and taxpayer awareness affect taxpayer compliance